2018
DOI: 10.1103/physrevlett.121.022501
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Ca60 and Implications For the Stability of Ca70

Abstract: The discovery of the important neutron-rich nucleus _{20}^{60}Ca_{40} and seven others near the limits of nuclear stability is reported from the fragmentation of a 345  MeV/u ^{70}Zn projectile beam on ^{9}Be targets at the radioactive ion-beam factory of the RIKEN Nishina Center. The produced fragments were analyzed and unambiguously identified using the BigRIPS two-stage in-flight separator. The eight new neutron-rich nuclei discovered, ^{47}P, ^{49}S, ^{52}Cl, ^{54}Ar, ^{57}K, ^{59,60}Ca, and ^{62}Sc, are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
85
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 42 publications
16
85
2
1
Order By: Relevance
“…As an important property of Ca isotopes, we first determined the odd and even driplines by seeing A dependence of S 1 and S 2 , and found that 64 Ca is an even-dripline nucleus and 59 Ca is an odd-dripline nucleus. As for E B in addition to S 1 , S 2 , our results agree with the experimental data [1][2][3][4] in 40−58 Ca. Our results are thus accurate enough for the prediction on the odd and even driplines.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As an important property of Ca isotopes, we first determined the odd and even driplines by seeing A dependence of S 1 and S 2 , and found that 64 Ca is an even-dripline nucleus and 59 Ca is an odd-dripline nucleus. As for E B in addition to S 1 , S 2 , our results agree with the experimental data [1][2][3][4] in 40−58 Ca. Our results are thus accurate enough for the prediction on the odd and even driplines.…”
Section: Discussionsupporting
confidence: 91%
“…Experimental data (crosses) are taken from Refs. [1][2][3]. The GHFB+AMP results are close to the GHFB ones (closed circles) for even Ca isotopes; in fact, the former deviates from the latter at most by 0.73 %.…”
Section: A Determination Of Even and Odd Driplines For Ca Isotopessupporting
confidence: 67%
See 1 more Smart Citation
“…4 for this peak. It may be seen that the physical nature of this excitation mode has strongly evolved compared to the case of 40 Ca. Now this excitation is mainly driven by neutrons.…”
Section: Ca Isotopes With Neutron Excessmentioning
confidence: 99%
“…In Sec. III we consider the case of the N = 20 N = Z nucleus 40 Ca to check whether a low-lying monopole excitation is predicted for this nucleus (having no neutron excess) and which is its nature. In the same section, more neutron-rich Ca isotopes are analyzed, 48 Ca (δ = (N − Z)/A = 0.17) and 60 Ca (δ = 0.33), and the evolution of the physical nature of the predicted low-lying strength is investigated going from N = 20 to N = 28.…”
Section: Introductionmentioning
confidence: 99%